2020
DOI: 10.1155/2020/9640103
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal (Pro)renin Receptor Expression and Serum Soluble (Pro)renin Receptor Concentration in Primary Aldosteronism

Abstract: The (pro)renin receptor [(P)RR] is a multifunctioning protein playing roles in various pathological conditions. A soluble form of (P)RR [s(P)RR] has been considered a biomarker for (P)RR expression in tissues. Expression of (P)RR has been described in aldosterone-producing adenoma (APA), but the roles of (P)RR have yet to be fully determined. This study investigated the significance of (P)RR and serum s(P)RR concentrations in patients with APA. We evaluated associations between (P)RR expression and expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Regarding the relationship between blood s(P)RR levels and metabolic and renal function factors, Hamada et al [ 18 ] reported higher blood s(P)RR levels in CKD patients with type 2 diabetes and hypertension. Watanabe et al [ 34 ] reported that blood s(P)RR levels are associated with renal damage in patients with primary aldosteronism, and Morimoto et al [ 16 ] reported that blood s(P)RR levels are associated with the severity of renal damage in patients with essential hypertension. These reports and the results of the present study may suggest that the s(P)RR is involved in insulin resistance and renal glomerular damage associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relationship between blood s(P)RR levels and metabolic and renal function factors, Hamada et al [ 18 ] reported higher blood s(P)RR levels in CKD patients with type 2 diabetes and hypertension. Watanabe et al [ 34 ] reported that blood s(P)RR levels are associated with renal damage in patients with primary aldosteronism, and Morimoto et al [ 16 ] reported that blood s(P)RR levels are associated with the severity of renal damage in patients with essential hypertension. These reports and the results of the present study may suggest that the s(P)RR is involved in insulin resistance and renal glomerular damage associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…fPRR belongs to the type I transmembrane receptor family, characterized by containing an interesting 28 kDa soluble PRR (sPRR) and generated by site-1 protease (S1P) [ 16 , 17 ]. Intensive clinical studies have proven that sPRR levels are significantly upregulated in various diseases and disease models, such as severe heart failure, hemodialysis maintenance, and primary aldosteronism, thus suggesting the value of sPRR as a biomarker [ 18 21 ]. sPRR is hypothesized to bind to specific ligands and receptors and mediate many signal transduction pathways [ 22 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…(P)RR protein levels are elevated in the subfornical organ of the brain of hypertensive humans [ 56 ], and brain (P)RR can regulate blood pressure by altering prohypertensive and antihypertensive pathways through local angiotensin-II-dependent and angiotensin-II-independent mechanisms [ 2 ]. Adrenal gland (P)RR is anticipated to contribute to adrenal aldosterone synthesis and the pathogenesis of hypertension [ 2 , 57 ], although the precise mechanism leading to the enhancement of aldosterone production remains unknown. In this study, we proposed that the IDR-containing hydrophobic grooves act as a protein binding site of (P)RR and allow multiple protein interactions.…”
Section: Discussionmentioning
confidence: 99%